Can Additional Information be Obtained from Claims Data to Support Surgical Site Infection Diagnosis Codes? - Warren, David K. (Infect Control Hosp Epidemiol, 2014)
OBJECTIVE: International Classification of Diseases (ICD-9-CM) diagnosis codes are increasingly used to identify healthcare-associated infections, often with insufficient evidence demonstrating validity of the codes used. Absent medical record verification, we sought to confirm a claims algorithm to identify surgical site infections (SSIs) by examining the presence of clinically expected SSI treatment. METHODS: We performed a retrospective cohort study using private insurer claims data from persons < 65 years with ICD-9-CM procedure or CPT-4 codes for anterior cruciate ligament (ACL) reconstruction from 1/2004–12/2010. SSIs occurring within 90 days after ACL reconstruction were identified by ICD-9-CM diagnosis codes. Antibiotic utilization, surgical treatment, and microbiology culture claims within 14 days of SSI codes were used as evidence to support the SSI diagnosis. RESULTS: Of 40,702 procedures, 401 (1.0%) were complicated by SSI, 172 (0.4%) of which were specifically identified as septic arthritis. Most SSIs were associated with an inpatient admission (n=232, 58%), and/or surgical procedure(s) for treatment (n=250, 62%). Temporally-associated antibiotics, surgical treatment procedures, and cultures were present for 84% (338/401), 61% (246/401), and 59% (238/401) respectively. Only 5.7% (23/401) of procedures coded for SSI post-procedure had no antibiotics, surgical treatments, or cultures within 14 days of the SSI claims. CONCLUSIONS: Over 94% percent of patients identified by our claims algorithm as having an SSI received clinically expected treatment for infection including antibiotics, surgical treatment, and culture, suggesting this algorithm has very good positive predictive value. This method may facilitate retrospective SSI surveillance and comparison of SSI rates across facilities and providers.